Mineralogy of Nickel and Cobalt Minerals in Xiarihamu Nickel–Cobalt Deposit, East Kunlun Orogen, China - Han, Yixiao; Liu, Yunhua; Li, Wenyuan (Frontiers in Earth Science, 2020)
Located in the East Kunlun Orogen, China, the Xiarihamu magmatic nickel–cobalt sulfide deposit is the country’s second largest deposit of this type. It was formed in special early Paleozoic with low copper grade (0.14 wt%) compared with other deposits of the same type. The mineralogy of nickel and cobalt minerals, which are direct carriers of these elements, can clearly reflect their behavior in the process of mineralization; however, such information for this deposit remains unreported. In the present study, we use an electron microscope and electron probe microanalyzer to delineate and analyze many nickel and cobalt minerals such as maucherite, nickeline, cobaltite, violarite, gersdorffite, parkerite, and arsenohauchecornite in various rocks and ores. With the increase in crustal material contamination, it can reach arsenide saturation locally in sulfide melt, then a separate Ni-rich arsenide (bismuth) melt exsolves somewhere. This melt will crystallize into nickeline, parkerite, arsenohauchecornite, and maucherite first. Second, most of nickel and cobalt tend to enter cobaltite and pentlandite phases, rather than existing in chalcopyrite and pyrrhotite phases as isomorphism during sufficient fractional crystallization of sulfide melt, which gathered nickel and cobalt elements widely. Also, more than one magma might result in the superposition of ore-forming elements. Later, the ore-forming elements redistribute limitedly through a hydrothermal process. The metallogenic mechanism model of nickel and cobalt established in the present study not only explains the process of nickel–cobalt mineralization in Xiarihamu but also can be applied to similar deposits and has a wide universal replicability.